(untitled) (Bulletin KNOB, 2014)
Although occasionally united, the Low Countries were and are a conglomeration of Dutch speaking states whose origins mostly lie in medieval times. Actually, the Low Countries coincide with the Netherlands, Flanders (the Dutch speaking part of Belgium) and the far north-western part of France. They are situated along the North Sea coast line and lie at the mouths of important rivers such as the Rhine, the Meuse and the Scheldt. Thanks to this excellent geographical situation the Low Countries have been one the most urbanized regions of Europe since medieval times. Since several decades, urban history is a booming discipline and it is studied from numerous perspectives, in the Low Countries as well as abroad. In the Low Countries, this flourishing state of affairs is in sharp contrast with the lack of academic interest in urban morphology. The analysis of medieval urban form receives only little attention from Dutch and Belgian scholars and there is a lack of comparative research. After reviewing published town atlases and related atlas series and urban monographs (Fig. 1), this article provides a comparative overview of urban genesis within the Low Countries, in an analysis of town plans by Jacob van Deventer (around 1550 - Figs. 3-9). From the 10th until the 14th century, an impressive number of towns of all kinds and sizes were established (Fig. 2). This is the period of town formation in the Low Countries. Until the 14th century, the Southern part of the Low Countries was the most important, but later the Northern part, especially Holland, gradually became the core area of urbanization. During the 14th century, new groups of towns blossomed in the North, while at the same time the genesis of towns in the South came to a standstill. These are only the first results of a very rough comparative analysis. To obtain a better insight and to explain the genesis of these groups of towns, and to get a grip on the urban form, more comparative and synthetic research is needed. This future research should focus on urban form and its transformations, not only within the context of general assumptions about economic prosperity and trading routes, but even more with regard to the genesis of various groups of towns with a comparable plan, their location in specific landscapes and well-intended policies by lords, merchants and burghers – all this in the light of processes of change, like the gradual shift of the genesis of towns from the South of the Low Countries to the North.